2021
DOI: 10.1021/acsami.1c13136
|View full text |Cite
|
Sign up to set email alerts
|

Additive Engineering for Efficient and Stable MAPbI3-Perovskite Solar Cells with an Efficiency of over 21%

Abstract: The high density of defects in MAPbI3 perovskite films brings about severe carrier nonradiative recombination loss, which lowers the performance of MAPbI3-based perovskite solar cells (PSCs). Here, methylamine cyanate (MAOCN) molecules were introduced into MAPbI3 solutions to manipulate the crystallizatsion of the MAPbI3 films. MAOCN molecules can slow down the volatilization rate of the solvent and delay the crystallization process of the MAPbI3 film. The crystal quality of the MAPbI3 films is effectively opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…This indicates that the F-type pseudo-halogen additives help the crystallization of the perovskite film, resulting in a larger grain size and a more uniform and smooth film. The gradually increasing (001) peak intensity and decreasing full width at half-maximum (fwhm) in Figure S1 and Table S1 further demonstrate that the perovskite films with the F-type pseudo-halogen additives have higher crystallinity and larger grain size Figure S2a–c show atomic force microscopy (AFM) images of the perovskite films.…”
Section: Resultsmentioning
confidence: 85%
“…This indicates that the F-type pseudo-halogen additives help the crystallization of the perovskite film, resulting in a larger grain size and a more uniform and smooth film. The gradually increasing (001) peak intensity and decreasing full width at half-maximum (fwhm) in Figure S1 and Table S1 further demonstrate that the perovskite films with the F-type pseudo-halogen additives have higher crystallinity and larger grain size Figure S2a–c show atomic force microscopy (AFM) images of the perovskite films.…”
Section: Resultsmentioning
confidence: 85%
“…One should refer to our previous reports for relevant experimental details. 27,28 For the semitransparent perovskite solar cell, the MoOx layer was thermally evaporated on the HTL layer in a vacuum chamber. Then the ITO was deposited by sputtering deposition at room temperature with a radiofrequency power of 70 W. Finally, the Ag metal grid was thermally evaporated on the ITO film.…”
Section: Methods and Characterizationsmentioning
confidence: 99%
“…All the materials and solvents were purchased from Advanced Election Technology Co. Ltd, Alfa Aesar, Xi’an Polymer Light Technology Corp and Sigma-Aldrich. 27,28…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they reported the hydrophobic nature of the MAOCN treated perovskite films. [197] Other ETLs: In search of novel organic ETL, Gu et al used 10,14-bis(5-(2-ethylhexyl)thiophen-2-yl)-dipyrido[3,2-a:2′,3′-c] [1,2,5]thiadiazolo [3,4-i]phenazine (TDTP) as ETL for inverted MAPbI 3 based PSCs and achieved a PCE of 18.2%. [198] Subsequently, Zhao et al reported hexaazatrinaphthylene (HATNA) derivatives as efficient ETL for MAPbI 3 based PSCs.…”
Section: The Role Of Etl In the Performance Of The Inverted Planar P-...mentioning
confidence: 99%